DAYA SAING EKSPOR INDUSTRI ALAS KAKI ANTARA INDONESIA DAN CHINA DI PASAR AMERIKA SERIKAT TAHUN 2011-2014 - Yunika "; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to explain the export competitiveness of footwear industry between Indonesia and China in the United States market in 2011-2014. Footwear is one of Indonesia's main export commodities. The value of Indonesian footwear exports is increasing every year, but Indonesia's footwear industry still has weaknesses to compete in the international market, especially in the US market. China is Indonesia's competitor in terms of footwear exports in the United States market because the largest export value of footwear in the United States comes from China.Data of this research was obtained from books, journals, articles, official documents and websites that support the hypothesis. The author used nation-state level analyze. The theories used in this research consist of comparative advantage theory by David Ricardo and competitiveness concept by Michael Porter.The result of this research shows that the competitiveness of Indonesia's footwear export industry is still below than the chinese footwear Industry. The competitiveness of a product is determined by the ability of an industry to innovate and improve its capabilities. The indicator of a competitively priced item consists of export value, price and regulation. Based on that concept, China's footwear industry has met the indicators as footwear industry that has competitiveness than Indonesia.Keywords: Competitiveness, Footwear, Export